THE EFFECTS OF ADDITIONAL PHYSICAL ACTIVITY PROGRAMMES ON MOTOR AND HEALTH RELATED COMPONENTS IN CASE OF STUDENTS IN 6TH GRADE - Norbert Csaba LUKÁCS; HANȚIU Iacob HANȚIU (Cluj University Press, 2019)
Introduction. According to a Eurydice report, in EU member states there are differences regarding the number of physical education classes held throughout a school year. Considering the number of EU physical education and health classes, in 2016, out of the total of 28 member states, Hungary occupied the 1st place and Romania the 21st place. Aims of the Research. This research aims to analyze the effects that additional physical activity programmes have on motor and health related components of students in 6th grade. Subjects and Methods. The research was performed on a sample group of 55 subjects, students in 6th grade, from two schools from Oradea, the additional programme using exercises and games with themes from handball, basketball, rugby-tag and badminton. We used two test batteries (EUROFIT and NETFIT) by which we measured the motor and health related components of physical fitness of the subjects involved in the research. The data was statistically analyzed using the SPSS software, version 20.0. In order to test the normality of the distribution of the data we used the Kolmogorov-Smirnov and Shapiro-Wilk tests, and to compare the mean values we used parametric and non-parametric tests, depending on the distribution: paired sample t-test or Wilcoxon signed-rank test. We also calculated the effect size (Cohen's d or eta-squared) with a confidence interval of 95%. Using the ANOVA analysis of variance, we calculated the variation between the scores and the mean values of the groups involved in the research. Results. Regarding the motor parameters with a normal distribution, the paired sample t-test shows that in case of experimental group A (EGA), after 7 months of additional physical activity, significant differences were recorded for 6 out of the 9 assessed parameters (plate tapping (PT), standing broad jump (SBJ), handgrip test (HT), sit-ups (STU), endurance shuttle run (ESR), paced push-ups (PPU)), while in case of experimental group B (EGB), the differences were recorded for 7 parameters (PT, SBJ, HT, sit-and-reach (SAR), shuttle run (SR), ESR, PPU, and in case of the control group (CG), for 5 parameters PT, SBJ, HT, ESR and trunk extension (TE). Conclusions. In EGA, in case of the nine assessment tests, the number of students located within the health zone increased by 5, in EGB this number increased by 13, and in the CG, by 3 subjects. We can establish that from this point of view the most efficient programme was the one applied to EGB. REZUMAT. Efectul unui program suplimentar de activități fizice asupra componentelor motrice și de sănătate ale elevilor din clasa a VI-a. Introducere. Potrivit unui raport Eurydice, în statele membre ale UE sunt diferențe privind numărul lecțiilor de educație fizică practicate într-un an școlar. În anul 2016, din totalul de 28 de state membre Ungaria a ocupat locul I iar România locul 21 privind numărul lecțiilor de educație fizică și de sănătate UE. Scopul cercetării. Scopul acestei cercetări l-a constituit analiza efectului unui program suplimentar de activități fizice asupra componentelor motrice și de sănătate ale elevilor de clasa a VI-a. Subiecți și metode. Cercetarea a avut loc pe un eșantion de 55 de subiecți, elevi de clasa a VI-a la două școli orădene, programul suplimentar utilizând exerciții și jocuri cu teme din handbal, baschet, rugby-tag și badminton. Au fost folosite două baterii de teste (EUROFIT și NETFIT) cu ajutorul cărora au fost măsurate componentele motrice și cele de sănătate ale fitnessului fizic al subiecților. Datele au fost analizate statistic cu ajutorul programului SPSS, varianta 20.0. În vederea testării normalității distribuției datelor s-a utilizat testele Kolmogorv-Smirnov și Shapiro-Wilk, iar pentru compararea mediilor s-au folosit teste parametrice sau nonparametrice, în funcție de distribuție: t-testul pentru eșantioane pereche sau testul Wilcoxon al rangurilor pereche. De asemenea, s-a calculat mărimea efectului (d a lui Cohen sau eta2), cu un interval de încredere de 95%. Cu ajutorul analizei de varianță ANOVA s-a calculat variația dintre scoruri și pe cea dintre mediile grupelor incluse în cercetare. Rezultate. Referitor la parametrii motrici cu distribuție normală, testul-t pentru eșantioane pereche ne arată că la GEA, după 7 luni de activități fizice suplimentare au fost înregistrate diferențe semnificative la 6 din cei 9 parametri evaluați (AP, SL, DM, RTA, CNR și FR), la GEB la 7 parametrii (AP, SL, DM, FT, CNA, CNR și FR), iar la GC la 5 parametrii (AP, SL, DM, CNR și ET). Concluzii. La GEA la cele nouă teste evaluate a crescut numărul de subiecți din zona de sănătate cu 5, la GEB cu 13, iar la GC cu 3 subiecți. Putem afirma că din acest punct de vedere cel mai eficient program a fost cel aplicat subiecților din GEB. Cuvinte cheie: componente motrice, componente de sănătate, fitnessul fizic, țesut adipos, clasa a VI-a.